The preparement of teacher for lifelong learning to fulfil social roles - Malinauskas, Romualdas (Acta Paedagogica Vilnensia, 1998)
This article gives the preparement of the teacher for lifelong learning to fulfil social roles. The reform of teacher training in Lithuania is waiting professional cooperating pedagogues. That’s why it is very important to discuss the lifelong learning of teacher’s in the new social structure of Lithuania. The teacher is a creator of another person, therefore he is to be his „self’ creator in the first place. In the research there were examined 338 students of Lithuanian Institute of physical education. The following roles were investigated: teacher, class manager, organiser, counsellor, collaborator. 64% students are prepared for lifelong learning of teachers role, 43% - of class manager role. One third of the students are prepared to fulfil the roles of counsellor and collaborator.